1975
DOI: 10.1063/1.431802
|View full text |Cite
|
Sign up to set email alerts
|

Radiative and nonradiative transitions in the first excited singlet state of simple linear aldehydes

Abstract: Nonradiative transitions in the first excited singlet state of perfluorocyclobutanone: Fluorescence decay times and fluorescence excitation spectroscopy Radiative and nonradiative transitions from the first excited singlet state of methylsubstituted naphthalenes Radiative and nonradiative rates of asymmetric linear aldehydes (C 2 -C 6 ) have been measured in the gas phase. Observe radiative lifetimes are compared to calculated radiative lifetimes obtained from the Strickler-Berg (SB) expression. The calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 14 publications
4
26
0
Order By: Relevance
“…The S 1 → S 0 (respectively, T 1 → S 0 ) transitions are predicted around 285 kJ/mol, i.e., near 420 nm (respectively, around 177 kJ/mol, ∼676 nm), in the typical range of fluorescence spectra of many aldehydes. 17 Note that the values found for S 1 -minCC, minTT, or minTG (from 282 to 290 kJ/mol, 413-424 nm) are very close to the fluorescence band measured in solution by Beeby et al (288 kJ/mol, 415 nm). 15 c. Relaxation pathways.…”
Section: S 1 and T 1 Excited State Calculationssupporting
confidence: 81%
See 1 more Smart Citation
“…The S 1 → S 0 (respectively, T 1 → S 0 ) transitions are predicted around 285 kJ/mol, i.e., near 420 nm (respectively, around 177 kJ/mol, ∼676 nm), in the typical range of fluorescence spectra of many aldehydes. 17 Note that the values found for S 1 -minCC, minTT, or minTG (from 282 to 290 kJ/mol, 413-424 nm) are very close to the fluorescence band measured in solution by Beeby et al (288 kJ/mol, 415 nm). 15 c. Relaxation pathways.…”
Section: S 1 and T 1 Excited State Calculationssupporting
confidence: 81%
“…Aldehydic compounds easily undergo intersystem crossing (ISC) from S 1 to T 1 upon electronic excitation. 17 This is also the case of GA as estimated by the spin-orbit coupling (23.4 cm −1 ) calculated in Ref. 5 for the structure at the minimum energy on S 1 .…”
Section: Theoretical Resultssupporting
confidence: 55%
“…aldehydes and ketones [24,25]. This is corroborated by the method derived in Section 4 to extract the total CH 2 O fluorescence from the CH 2 O spectral structure intensity.…”
Section: Methods Of Quantificationmentioning
confidence: 92%
“…Unfortunately, only data on the absorption spectra below typical cold flame temperatures were found. The absorption and emission spectra of aldehydes and some ketones (symmetrical methyl-substituted acetones) have been recorded by Hansen and Lee [24,25]. They show that these species fluoresce in the same wavelength range as CH 2 O but hardly absorb at 355 nm at room temperature.…”
Section: In a Spraymentioning
confidence: 98%
“…Fluorescence from the excited singlet state occurs with quantum yields of (0.1-1.8) 10 À3 in the wavelength region covered. [43] This contribution is small and can be neglected here. Gandini and Hackett [44] have shown that intersystem crossing S 1 !T 1 * occurs at low pressures of acetaldehyde in the absence of added quenching gas.…”
Section: Discussionmentioning
confidence: 99%